The development and initial validation of the Health and Reproductive Survey (HeRS). (August 2021) - Duffy, Donna; Yourkavitch, Jennifer; Bruinvels, Georgie; Rinaldi, Nicola J; Wideman, Laurie
Background: Due to the diversity in profiles associated with the female reproductive cycle and their potential physiological and psychological effects, monitoring the reproductive status of exercising females is important from a practical and research perspective. Moreover, as physical activity can influence menstrual function, the effects of physical activity energy expenditure on reproductive function should also be considered. Aim: The aim of this study was to develop and establish initial face and content validity of the Health and Reproductive Survey (HeRS) for physically active females, which is a retrospective assessment of menstrual function from menarche (first menstruation) to menopause (cessation of menstruation). Methods: Face validity was evaluated qualitatively, and the initial content validity was established through a principal component analysis. The face validity process was completed by 26 females aged 19–67 years and the content validity was established through a survey sent to a convenience sample of 392 females, of which 230 females (57.9% and aged 18–49 years) completed the survey. Results: The revisions made following the face validation improved the understanding, flow, and coherence of the survey. The principal component analysis indicated that, at a minimum, the survey measures these constructs: menstrual cessation and associated moderators, athletic participation and performance levels (as associated with menstruation change and the menstrual cycle), age and menstrual cessation, hormonal contraception ("birth control"), and menarche and associated moderators. Conclusion: The Health and Reproductive Survey (HeRS) is a partially validated tool that can be used by researchers to characterize the menstrual status of physically active females relative to their physical activity status.